Akibat Hukum terhadap Perceraian yang dilakukan di Luar Pengadilan Agama Merlung Kabupaten Tanjung Jabung Barat - Maryati Maryati (Universitas Batanghari Jambi, 2022)
Divorce is not the end of a household life but divorce is the beginning of new problems in domestic life, for couples who live it, this is an obligation for the parties of the couple who live a life full of problems that will be held accountable, one of which is divorce that What happened in Merlung village is a problem that will be discussed here with regard to divorce which is carried out outside the court, this has an impact on the lives of each party, where here it is demanded the rights and obligations of the husband who decides the divorce, will be responsible for his children and wife , as well as joint property. If the divorce is carried out outside this court, it is feared that all of these rights cannot be carried out properly and perfectly, where the rights that are obligations are difficult to implement, because they do not have legal force that binds them, so that these rights cannot be implemented properly. with other rights.